Implementation of LABSTER virtual lab in immunology for innovative teaching and improved learning in veterinary degree - Casado, Javier G.; Tarazona, Raquel; Cordero, Hector (Frontiers in Veterinary Science, 2025)
Virtual laboratories provide a risk-free environment for students to conduct experiments, particularly those involving hazardous materials or complex procedures. Previous studies have shown that gamified elements and interactive tools enhance the interest of students and promote active participation. In the case of Immunology in the veterinary degree, our prior observations indicate that veterinary students experience learning difficulties with topics related to molecules and effector functions of the immune system. This study aimed to investigate the utility of virtual laboratory simulations for teaching Immunology. For that purpose, cohorts of second-year veterinary students and third-year biochemistry students at the University of Extremadura were surveyed before and after the implementation of the LABSTER virtual lab in the Immunology course. The survey questions addressed their perceptions of virtual environments, prior computer knowledge, experiences with virtual platforms for learning, ethics, comparisons to traditional lab practices, and the perceived utility of virtual labs for their future careers. Gender differences were considered to determine potential variations in perceptions of virtual learning. Results indicated that veterinary students had no prior experience with LABSTER or similar virtual tools in other courses. Initially, nearly half of the students felt “unprepared” to use such tools. Notably, all students rated the experience using LABSTER virtual lab with an average of 7.5 ± 1.4 and 8.1 ± 1.8, in men and women, respectively. Indeed, most students perceived that LABSTER was useful for learning Immunology. Most students were hesitant about fully replacing traditional labs with virtual tools but found LABSTER beneficial for their future career skills. In conclusion, while virtual simulations are not a complete substitute for hands-on laboratory experiences, they may effectively help students develop practical skills and familiarize themselves with laboratory procedures and equipment. These findings highlight the potential of virtual labs as a complementary tool in veterinary education.